Issues and Emerging Trends in Identity Management (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In todays digital age as companies are moving more and more amounts of important, sensitive data, information, applications, and infrastructure online there is a need toestablish and maintain credentials on all the connected and disconnected systems, and grant rights or access to users. The main goal is to manage physical and logical resources and relate them to owners. Identity Management is emerging as a significant technology to help in handling the complexity of todays Business companies, dealing with security in thevirtualized environment, strong authentication and dealing with threats from Insiders. This paper attempts to provide direction toward some of the issues, Challenges and Trends in Identity Management. Emerging Trends in Information technology involves identity audit, automated compliance, Role lifecycle management, authorization, Information centric identity, E-SSO and strong authentication, Open ID, Infocards, CardSpace, Governance, Identity management as a service, Risk management, and Compliance Modularity.